Selective depletion of virus-specific CD8 T cells from the liver after PD-1 therapy with Fc-intact antibody during chronic infection - Masao Hashimoto; Tahseen H. Nasti; Hyun-Tak Jin; Melissa Bu; Koichi Araki; Junghwa Lee; Rajesh M. Valanparambil; Akil Akhtar; Mohammad Affan Khan; Zhipeng Peng; Yinghong Hu; Daniel T. McManus; et al. (Proceedings of the National Academy of Sciences, 2026)
Anti-programmed cell death 1 (PD-1) antibody therapy is now widely used in various cancers. However, the role of the antibody Fc region in PD-1 directed immunotherapy is not well understood. Preclinical studies commonly use species-mismatched rat anti-mouse antibodies, which may not accurately reflect antibody-Fc gamma receptor (FcγR) interactions. Here, we used mouse anti-mouse PD-1 antibodies to investigate how the Fc region influences therapeutic efficacy for enhancing CD8 T cell responses using mouse models of chronic lymphocytic choriomeningitis virus infection and CT26 tumors. Treatment with these mouse anti-mouse PD-1 antibodies caused preferential depletion of PD-1+ virus-specific CD8 T cells in the liver, resulting in increased viral titers. These effects of mouse anti-PD-1 antibodies were Fc dependent since mutating the Fc region to block FcγR interaction prevented PD-1+ CD8 T cell depletion and resulted in effective immunotherapy. Using mice lacking activating FcγR III or inhibitory FcγR IIb, we found that depletion of PD-1+ CD8 T cells was mediated via activating FcγR III. Furthermore, we determined that phagocytic cells, not natural killer cells, were the in vivo effectors that mediated depletion of PD-1+ CD8 T cells. Similar depletion of tumor-specific CD8 T cells and reduced tumor control were observed in the CT26 model with Fc-intact mouse anti-mouse PD-1 treatment. These findings highlight potential negative effects of Fc-functional anti-PD-1 antibodies in therapies for liver cancer, liver metastases, and chronic hepatotropic viral infections. Conversely, FcγR-mediated depletion could benefit “agonistic” anti-PD-1 antibodies for treatment of autoimmunity. Our research emphasizes the importance of Fc region in tailoring PD-1 therapies for diverse clinical applications.